The Impact of Rising Oil Prices on U.S. Inflation and Inflation Expectations in 2020-23 - Lutz Kilian; Xiaoqing Zhou (Center for Economic Studies and ifo Institute (CESifo), 2021)
Predictions of oil prices reaching 100 per barrel during the winter of 2021/22 have raised fears of persistently high inflation and rising inflation expectations for years to come. We show that these concerns have been overstated. A 100 oil scenario of the type discussed by many observers, would only briefly raise monthly headline inflation, before fading rather quickly. However, the short-run effects on headline inflation would be sizable. For example, on a year-over-year basis, headline PCE inflation would increase by 1.8 percentage points at the end of 2021 under this scenario, and by 0.4 percentage points at the end of 2022. In contrast, the impact on measures of core inflation such as trimmed mean PCE inflation is only 0.4 and 0.3 percentage points in 2021 and 2022, respectively. These estimates already account for any increases in inflation expectations under the scenario. The peak response of the 1-year household inflation expectation would be 1.2 percentage points, while that of the 5-year expectation would be 0.2 percentage points.
Keywords: E31; E52; Q43; 330; scenario; inflation; expectation; oil price; gasoline price; household survey; core; pandemic; recovery